Pengembangan Learning Management System sebagai Media Pembelajaran Sistem Informasi Manajemen bagi Divisi Teknologi Informasi di PT Globalindo Intimates - Risqi Bagus Palevi; Nurkhamid (Department of Electronics and Informatics Engineering Education, 2024)
This research aims to develop a Learning Management System as a Learning Media for Management Information Systems for employees in the Information Technology Division at PT Globalindo Intimates and to test the feasibility of the Learning Management System application as a Learning Media for Management Information Systems for employees in the Information Technology Division. The method used in this research is the Research and Development (R&D) method. This method is supported by the 4D development model adapted from Thiagarajan. The 4D model consists of define, design, develop, and disseminate stages. Data collection is conducted using questionnaires in the form of assessments from subject matter experts, media experts, and ISO 19796-1 testing by users, namely employees in the Information Technology Division at PT Globalindo Intimates The results of the research state that the Learning Management System as a Learning Media for Management Information Systems for employees in the Information Technology Division at PT Globalindo Intimates has been developed and acceptable as learning media also received an